Bifidobacterial β-Galactosidase-Mediated Production of Galacto-Oligosaccharides: Structural and Preliminary Functional Assessments - Ambrogi, Valentina; Bottacini, Francesca; Mac Sharry, John; van Breen, Justin; O’Keeffe, Ellen; Walsh, Dan; Schoemaker, Barry; Cao, Linqiu; Kuipers, Bas; Lindner, Cordula; Jimeno, Maria Luisa; Doyagüez, Elisa G.; et al. (Frontiers in Microbiology, 2021)
In the current study the ability of four previously characterized bifidobacterial β-galactosidases (designated here as BgaA, BgaC, BgaD and BgaE) to produce galacto-oligosaccharides (GOS) was optimized. Of these enzymes, BgaA and BgaE were shown to be promising candidates for GOS production (and the corresponding GOS mixtures were called GOS-A and GOS-E, respectively) with conversion efficiencies of 19.0 % and 40.3 %, respectively. GOS-A and GOS-E were partially purified and structurally characterized. NMR analysis revealed that the predominant (non-lactose) disaccharide was allo-lactose in both purified GOS preparations. The predominant trisaccharide in GOS-A and GOS-E was shown to be 3’-galactosyllactose, with lower levels of 6’-galactosyllactose and 4’-galactosyllactose. These three oligosaccharides have also been reported to occur in human milk. Purified GOS-A and GOS-E were shown to be able to support bifidobacterial growth similar to a commercially available GOS. In addition, GOS-E and the commercially available GOS were shown to be capable of reducing Escherichia coli adhesion to a C2BBe1 cell line. Both in vitro bifidogenic activity and reduced E. coli adhesion support the prebiotic potential of GOS-E and GOS-A.